2018
DOI: 10.1364/oe.26.023207
|View full text |Cite
|
Sign up to set email alerts
|

Efficient enhancement of bismuth near infrared luminescence by the co-doping of tantalum in GYAP crystal

Abstract: Bi/Ta double doped GdYAlO (Bi/Ta:GYAP) near-infrared (NIR) laser crystal was successfully grown. The codoping of Ta was demonstrated to effectively enhance the NIR fluorescence emission in Bi/Ta:GYAP crystal for the first time. The introduced Ta ion can induce the change of valence states from Bi to Bi based on the charge compensation mechanism, bringing about the enhanced NIR fluorescence emission. The three NIR fluorescence emission peaks centering at 1005, 1195, and 1280 nm were ascribed to three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In 2018, Zhang and co-workers synthesized Yb/Bi co-doped PbF 2 single crystal using Bridgman method ( Zhang et al., 2018a , 2018b ). Figure 3 shows the NIR emission spectra of prepared samples.…”
Section: Known Bi-doped Nir Luminescent Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Zhang and co-workers synthesized Yb/Bi co-doped PbF 2 single crystal using Bridgman method ( Zhang et al., 2018a , 2018b ). Figure 3 shows the NIR emission spectra of prepared samples.…”
Section: Known Bi-doped Nir Luminescent Crystalsmentioning
confidence: 99%
“…However, the authors found efficient NIR luminescence if co-doped with Yb 3+ ions, in which energy transfer from Yb to Bi should explain this phenomenon ( Xiong et al., 2012 ). Another way to enhance NIR emission has also been reported in Bi/Ta co-doped Gd 0.1 Y 0.9 AlO 3 single crystal, because the introduction of Ta 5+ can effectively lead to the change of valence states from Bi 3+ to Bi + based on the charge compensation mechanism ( Zhang et al., 2018a , 2018b ).…”
Section: Known Bi-doped Nir Luminescent Crystalsmentioning
confidence: 99%
“…Efficient near-infrared photo-luminescence has attracted more and more attention for the promising applications in optical fiber communication [1], remote sensor [2], biological imaging [3], and laser guide stars [4] , etc. So these laser materials have become study focus [5][6][7].…”
Section: Introductionmentioning
confidence: 99%